Leontius of Neapolis and the stories about Peter the Publican (Circe de clásicos y modernos, 2019)
In the Leontius’ Life of John the Almsgiver, chapters 20-21 of the long version (= 22 of the short version), the protagonist adds a tale about Peter the Publican. Déroche, when he enumerates the manu-scripts of the Leontius’ works, includes two that do not fall to them; they testify a tale about the same subject but different.
Keywords: Leontius; John the Almsgiver; Peter the Publican; manuscript tradition